Evaluation of the Basic Urban Aspects in the Sustainable Urban Development and Improvement of Quba Road in Medina (Darb Al-Sunna) - Waheeb, Sahl (Journal of King Abdulaziz University: Environmental Design Sciences, 2025)
In recent years, the Medina region has witnessed remarkable development in infrastructure and the establishment of distinguished urban projects by and under the supervision of many parties such as the Medina Development Authority and Al-Maqar Company, the investment arm of Medina Municipality. This development aims to enhance the status of Medina as a basic religious destination with a planning and urban system. It contributes to achieving the Kingdom’s Vision 2030, but some of the main areas and axes of Medina remain developed to a very limited extent, including Quba Avenue from the south of the Prophet’s Mosque to Quba Mosque, where the Quba Avenue road was formed in the previous period before it was limited to pedestrian traffic only during the previous year’s one of the most important commercial hubs in Medina. The road currently faces a major challenge in restoring commercial activity to what it was previously. This study aims to evaluate five main urban aspects of urban humanization Quba Road redevelopment and improvement project to ensure its feasibility in shaping a humanized and sustainable urban environment. The five basic aspects are the attractiveness of the retail facades at the ground floor level, the attractiveness of the commercial activity, the attractiveness of the pedestrian infrastructure, the accessibility of the road, and the type of parking spaces currently available. The study concluded that the attractiveness of destinations, commercial activities, and the development of parking lots are among the most important aspects that must be developed. It also recommends subsequent research into developing attractive urban spaces and squares.